(untitled) (Baghdad Science Journal, 2023)
The accumulation of toxic elements in vegetables and melons grown in agriculture, Brassica rapa - turnip, Solanum lycopersicum - tomato, Citrullus lanatus - watermelon, Capsicum annuum - bell pepper, Daucus carota - carrots, Cucurbita pepo - pumpkin, Cucumis melo - melon, and also Prunus armeniaca - apricot from fruit trees were analyzed. The excess of maximum allowable concentrations in agricultural crops of the element As by 1.65-1.75, Cd - 1.6-2.3, Cr -1.2-2.35, Cu -1.6-3.3, Ni - 1.16-3.53, Pb - 1.54-3.08, Al - 1.36-3.5, Sb - 2.0-33, Se - 1.1-3.3 times was established. The maximum allowable concentration of mercury in vegetables and melons was equal to 0.02 mg/kg, and in the chosen plants this indicator was close to the maximum allowable concentration (MAC). An ecological series of vegetable and melon crops (tomatoes → pumpkin → turnips → bell peppers → melons → watermelons → carrots) has been developed for their placement on fields contaminated with heavy metals Se, As, Pb, Cd, Zn, included in the first class in terms of the degree of danger to human health, while Ni, Cu, Cr metals were from the second class, and metal Mn from the third class. Agricultural crops in the ecological series are placed in inverse proportion to the regularities of the hyper accumulation of heavy metals in them.